The secretome of the fish pathogen Tenacibaculum maritimum includes soluble virulence-related proteins and outer membrane vesicles - Escribano, M. Pilar; Balado, Miguel; Toranzo, Alicia E.; Lemos, Manuel L.; Magariños, Beatriz (Frontiers in Cellular and Infection Microbiology, 2023)
Tenacibaculum maritimum, the etiological agent of tenacibaculosis in marine fish, constitutively secretes extracellular products (ECPs) in which protein content has not been yet comprehensively studied. In this work, the prevalence of extracellular proteolytic and lipolytic activities related to virulence was analyzed in 64 T. maritimum strains belonging to the O1–O4 serotypes. The results showed the existence of a great intra-specific heterogeneity in the enzymatic capacity, particularly within serotype O4. Thus, the secretome of a strain belonging to this serotype was characterized by analyzing the protein content of ECPs and the possible production of outer membrane vesicles (OMVs). Notably, the ECPs of T. maritimum SP9.1 contain a large amount of OMVs that were characterized by electron microscopy and purified. Thus, ECPs were divided into soluble (S-ECPs) and insoluble fractions (OMVs), and their protein content was analyzed by a high-throughput proteomic approach. A total of 641 proteins were identified in ECPs including some virulence-related factors, which were mainly found in one of the fractions, either OMVs or S-ECPs. Outer membrane proteins such as TonB-dependent siderophore transporters and the type IX secretion system (T9SS)-related proteins PorP, PorT, and SprA appeared to be mainly associated with OMVs. By contrast, putative virulence factors such as sialidase SiaA, chondroitinase CslA, sphingomyelinase Sph, ceramidase Cer, and collagenase Col were found only in the S-ECPs. These findings clearly demonstrate that T. maritimum releases, through surface blebbing, OMVs specifically enriched in TonB-dependent transporters and T9SS proteins. Interestingly, in vitro and in vivo assays also showed that OMVs could play a key role in virulence by promoting surface adhesion and biofilm formation and maximizing the cytotoxic effects of the ECPs. The characterization of T. maritimum secretome provides insights into ECP function and can constitute the basis for future studies aimed to elucidate the full role of OMVs in the pathogenesis of fish tenacibaculosis.